PERSONAL INCOME TAXES IN BULGARIA, HUNGARY AND ROMANIA:A BUSINESS CYCLE PERSPECTIVE - Krumov Todorov , Ivan (Revista Inclusiones, 2020)
Employing quarterly seasonally adjusted Eurostat data for the period 1995-2020, the Hodrick-Prescott filter and the correlations between the output gap and the changes in the trend shares and the cyclical shares of total income tax revenue in GDP, this paper attempts to compare the cyclical impact of progressive and proportional income taxes in Bulgaria, Hungary and Romania. The research results imply that in Hungary discretionary and automatic changes in income tax revenue are countercyclical under both progressive and proportional taxation but income tax discretion and automatic stabilizers are more effective under progressive taxation. In Bulgaria discretionary and automatic changes in income tax revenue are procyclical under proportional taxation and countercyclical under progressive taxation. In Romania, discretionary changes in income tax revenue are procyclical under both progressive and proportional taxation but automatic changes in income tax revenue exacerbate cyclical fluctuations under proportional taxation and mitigate business cycle volatility under progressive taxation. It may be inferred that in all three analyzed countries, the efficiency of income tax discretion and automatic stabilizers under progressive taxation is higher than under proportional taxation. From a business cycle standpoint, it is advisable that Bulgaria, Hungary and Romania switch from proportional to progressive income taxation.